Transformasi Pembelajaran Biologi Menggunakan Video Animasi: Dampaknya terhadap Motivasi dan Pemahaman Konsep Siswa Pada Materi Klasifikasi Makhluk Hidup - Shebianda Meiny Warow; Aser Yalindua; Zusje W. M. Warouw (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Low motivation to learn and limited conceptual understanding are significant challenges in learning biology at the junior high school level, especially in abstract material on the classification of living things. This study aims to analyze the influence of the use of animated videos on student learning motivation and learning outcomes. A quantitative approach with a pre-experimental design of one group pre-test and post-test was used in this study. The research sample consisted of 25 students in grade VIII of SMP Negeri 2 East Likupang. Data was collected through observation sheets to assess learning motivation and pre-test and post-test tests to evaluate learning outcomes. The results of the observation showed that the average motivation of students reached 86.32% in the outstanding category. The average pre-test score of 59.57 increased to 81.09 on the post-test, indicating a significant improvement in concept comprehension. The t-test corroborates these findings with a significant value at a 95% confidence level. These results show that animated videos can present a visualization of complex concepts in an engaging and contextual way, thereby increasing students' focus, active participation, and absorption of the material. In addition, the use of this media also supports the development of students' collaborative skills and critical thinking. This research confirms that animated videos are a strategic alternative in effective science learning, especially in school environments with limitations of conventional visual media. It is suggested that the application of this media be expanded to various materials and levels of education.